Probing the Sources of Uncertainty in Transient Warming on Different Timescales. Issue 20 (22nd October 2019) - Lutsko, Nicholas J.; Popp, Max
Abstract: The rate of transient warming is determined by a number of factors, notably the radiative forcing from increasing CO2 concentrations and the net radiative feedback. Uncertainty in transient warming comes from both the uncertainty in each factor and from the warming's sensitivity to uncertainty in each factor. An energy balance model is used to untangle these two components of uncertainty in transient warming, which is shown to be most sensitive to uncertainty in the forcing and not to uncertainty in radiative feedbacks. Additionally, uncertainty in the efficacy of ocean heat uptake is more important than uncertainty in the rate of ocean heat uptake. Three further implications are as follows: (1) transient warming is highly sensitive to uncertainty in emissions, (2) caution is warranted when extrapolating future warming trends from short‐lived climate perturbations, and (3) climate models tuned using the historical record are highly sensitive to assumptions made about the historical forcing. Key Points: Transient warming is most sensitive to uncertainty in the radiative forcing and not to uncertainty in the radiative feedbacks Reducing uncertainty in the radiative forcing is the most efficient way of reducing uncertainty in transient warming Radiative feedbacks of climate models that are tuned to the historical record are highly sensitive to the assumed historical forcing